Double diffusive nanofluid flow in a duct with cavity heated from below - Hussain, S.; Öztop, Hakan Fehmi; Jamal, M.; Hamdeh, N. A. (Pergamon-Elsevier Science Ltd, 2017)
A computational work has been done on double diffusive nanofluid flow in a duct with cavity heated from below numerically. Solution of governing equation was performed via the Galerkin finite element method. Newton method is utilized to cope with discretized nonlinear systems of equations and the Gaussian elimination method has been applied to solve the associated linear subproblems in each nonlinear iteration. Results are performed for different governing parameters as nanoparticle volume fraction from 0 to 0.04, Reynolds number from 1 to 200, Hartmann number from 0 to 100, Richardson number from 0.01 to 100 and buoyancy ratio from 0 to 10. It is found that both average Sherwood and Nusselt number are increased with increasing of nanoparticle volume fraction and decreased with Hartmann number. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Double diffusive; Channel with a cavity; Magnetic field; Galerkin FEM; Numerical simulation